HRM practices and employee satisfaction in Real Estate business: a study on Vision 21 Design and Developments Ltd. - Rushdi, Iftekhar Hossain (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2013.